Technology policy and the development of small and medium scale enterprises in contemporary Nigeria - Oladeji, S. I.
The author feels that Government intervention should be considered to be more effective than the development of local technological capability for the prosperity of SME's in Nigeria. Efforts are required in policy formulation and implementation.
Since 1986, Nigeria's industrialisation policies have continued to be influenced by the structural adjustment programme with its concomitant market-oriented economic policies. There has been the implementation of the privatisation and commercialisation policy while the country's industrial strategy has hinged on the development of small and medium scale enterprises (SME). It is, however, the contention of this paper that, for the development of local technological capabilities in SME, exclusive reliance on market forces is not as effective as a determined and concerted government intervention. Against this thesis, the paper reviews and analyses industrialisation and technology policies in the light of the scope and prospects they afford for revitalising SME in Nigeria. In terms of enactments, industrialisation policies were found to be well focused and have ample scope for the development of SME. Technology policies, on the other hand, lack selectivity and are less focused on the promotion of SME in the country. The conclusion is reached that the design and implementation of technology policy have to be reviewed and aligned with the country's industrialisation policies. Specifically, in policy formulation and implementation, concerted efforts are needed to generate, and at the same time create, effective social demand for science and technology.
Keywords: Technology policy; Small and medium scale enterprises--Nigeria.